URANIUM IN SUPERGENE PHOSPHORITES - Zanin Yu.N.; Zamirailova A.G. (My University, 2007)
The distribution of uranium was studied in supergene phosphorites from the zones of the weathering of sedimentary and endogenous rocks, as well as in nonmarine coprolitic phosphorites and, to a lesser extent, phosphorites from ocean islands. These phosphorites show a diversity of the composition of their carbonate-apatite and structural characteristics. The uranium content ranges mostly from 5 to 100 ppm, with minimum and maximum values of 0.5 and 790 ppm. There is no correlation between the uranium content of a phosphorite and the type of rock with which it is connected. Lacustrine coprolitic phosphorites show elevated uranium contents (about 200 ppm). The maximum uranium content was detected in finely laminated phosphorite encrustations. The correlation analysis of the whole data set (63 samples) showed that uranium content is not correlated with any other component of phosphorites at a confidence level of 0.95. In contrast, there is a correlation between U and P2O5, CaO, and F for the combined set of samples from southern Siberian deposits. The significant correlation of U with Na2O and CO2 is variable both for southern Siberia on the whole and for particular deposits from this region.